2022
DOI: 10.3389/fped.2022.883620
|View full text |Cite
|
Sign up to set email alerts
|

Practicing Level and Determinants of Safe Cord Care and Skin-To-Skin Contact Among Post-partum Women in Public Hospitals of Eastern Ethiopia

Abstract: BackgroundEven though practicing levels of safe cord care and skin-to-skin contact among post-partum women are critical to reducing neonatal deaths, limited data revealed the low practice. Thus, the purpose of this study was to determine the level of practice and determinants of safe cord care and skin-to-skin contact among post-partum women in public hospitals of Eastern Ethiopia.MethodsA facility-based cross-sectional study was conducted at the public hospitals of Harari reginal state, eastern Ethiopia. A ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 34 publications
(41 reference statements)
0
7
1
Order By: Relevance
“…In this study, 13.70% of mothers applied potentially harmful substances, such as dung, oil, ointments, ash, and butter on the umbilical stump of the neonates. This finding was lower than the studies done in Benin City (46.1%) ( 17 ), Nigeria (22.2 and 67.3%) ( 18 , 19 ), Nepal (26 and 43%) ( 28 ), Uganda 39.6% ( 3 ), Southwest Ethiopia (20.4 and 54.7%) ( 20 , 23 ), and Eastern Ethiopia (29.3%) ( 24 ). The discrepancy may be due to variations in access to awareness, geographical variations, and health-seeking behavior across the different cultural beliefs.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In this study, 13.70% of mothers applied potentially harmful substances, such as dung, oil, ointments, ash, and butter on the umbilical stump of the neonates. This finding was lower than the studies done in Benin City (46.1%) ( 17 ), Nigeria (22.2 and 67.3%) ( 18 , 19 ), Nepal (26 and 43%) ( 28 ), Uganda 39.6% ( 3 ), Southwest Ethiopia (20.4 and 54.7%) ( 20 , 23 ), and Eastern Ethiopia (29.3%) ( 24 ). The discrepancy may be due to variations in access to awareness, geographical variations, and health-seeking behavior across the different cultural beliefs.…”
Section: Discussioncontrasting
confidence: 58%
“…However, many pieces of evidence from Ethiopia and other low-and middle-income countries have shown that mothers apply substances, such as butter, hot fermentation, lantern wax, fish bone, toothpaste, ash, charcoal, oils, vaseline, saliva, red sand, menthol-containing balm, traditional medicine, and cow dung (3,11,(17)(18)(19)(20)(21)(22)(23)(24)(25). These practices often take place under unsterilized conditions; hence, they increase the risk of umbilical infection and neonatal tetanus.…”
Section: Introductionmentioning
confidence: 99%
“…The level of skin-to-skin care practice and its determinants among postnatal mothers in Ethiopia were examined in eight cross-sectional studies that made up this study. The studies were released in the years 2017 [ 6 ] through 2022 [ 7 , 20 , 21 ]. Of all studies, two studies were conducted at the national level [ 22 , 23 ], two studies were from the Oromia region [ 20 , 21 ], two studies were from Harari regional state [ 7 , 24 ], one study was from Tigray [ 6 ] and one study was from Southern Nation Nationalities and people of Ethiopia [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies were released in the years 2017 [ 6 ] through 2022 [ 7 , 20 , 21 ]. Of all studies, two studies were conducted at the national level [ 22 , 23 ], two studies were from the Oromia region [ 20 , 21 ], two studies were from Harari regional state [ 7 , 24 ], one study was from Tigray [ 6 ] and one study was from Southern Nation Nationalities and people of Ethiopia [ 8 ]. The sample size of the included studies ranged from 286 in a study done in Oromia [ 20 ] to a maximum of 7488 in a study conducted at the national level [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation